Use of Mass Spectrometry to Screen Glycan Early Markers in Hepatocellular Carcinoma - de Oliveira, Raphaela Menezes; Ornelas Ricart, Carlos Andre; Araujo Martins, Aline Maria (Frontiers in Oncology, 2018)
Association between altered glycosylation patterns and poor prognosis in cancer reveal glycans as potential specific tumor markers. Most proteins are glycosylated and functionally arranged on cell surface and extracellular matrix, mediating interactions and cellular signaling. Thereby, aberrant glycans may be considered a pathological molecular modification as important as changes in protein expression for cancer and other complex diseases. As most serum glycoproteins have hepatic origin, liver disease phenotypes, such as hepatocellular carcinoma (HCC), may present altered glycan profile and display important modifications. The characterization of glycomic profiles in pathological conditions by mass spectrometry (MS) may lead to the discover of early diagnostic markers using non-invasive approaches. Mass spectrometry is a powerful analytical technique capable of elucidating many glycobiological issues and overcome limitations of the serological markers currently applied in clinical practice. Therefore, MS-based glycomics of HCC biomarkers is a promising tool to increase early detection and monitoring this complex disease.